Diseño y construcción de un prototipo de máquina clasificadora de café seco y trillado. - Rosales Aranda, Gabriel Renato (2022)
The present project is about the design and construction of a "coffee bean threshing and sorting machine", and it had as its main object, of offering a technological and accurate tool for the bean sorting activity in the local coffee industry. For this, and before the design of every main part of the machine, full information searching about threshing and coffee sorting was made, as well as a study of the capacity required for the machine for the local production, it was possible to design and built all the main and secondary machine parts. For these, and other construction reasons, the machine was built with a slider-crank mechanism, giving vibration to the three-size-graders plates. Finally, the machine was tested with local coffee beans, having very good results in terms of accuracy. Keywords: prototype, coffee, sorting, threshing, machine, vibration.